Size Control and Improved Aqueous Colloidal Stability of Surface-Functionalized ZnGa2O4:Cr3+ Bright Persistent Luminescent Nanoparticles - Serge-Correales, York E. [UNESP]; Neumeyer, David; Ullah, Sajjad; Mauricot, Robert; Zou, Qilin; Ribeiro, Sidney J. L. [UNESP]; Verelst, Marc (American Chemical Society (ACS), 2023)
Near-infrared (NIR)-emitting ZnGa2O4:Cr3+ (ZGO) persistent luminescent nanoparticles (PLNPs) have recently attracted considerable attention for diverse optical applications. The widespread use and promising potential of ZGO material in different applications arise from its prolonged post-excitation emission (several minutes to hours) that eliminates the need for continuous in situ excitation and the possibility of its excitation in different spectral regions (X-rays and UV-vis). However, the lack of precise control over particle size/distribution and its poor water dispersibility and/or limited colloidal stability required for certain biological applications are the major bottlenecks that limit its practical applications. To address these fundamental limitations, herein, we have prepared oleic acid (OA)-stabilized ZGO PLNPs with controlled size (7-12 nm, depending on the type of alcohol used in synthesis) and monodispersity. A further increase in size (8-21 nm), with a concomitant increase in persistent luminescence, could be achieved using a seed-mediated approach, employing the as-prepared ZGO PLNPs from the first synthesis as the seed and growing layers of the same material by adding fresh precursors. To remove their surface oleate groups and make the nanoparticles hydrophilic, two surface modification strategies were evaluated: modification with only poly(acrylic acid) (PAA) as the hydrophilic capping agent and modification with either PAA or cysteamine (Cys) as the hydrophilic capping agent in conjunction with BF4- as the intermediate surface modifier. The latter surface modifications involving BF4- conferred long-term (60 days and longer) colloidal stability to the nanoparticles in aqueous media, which is related to their favorable ζ potential values. The proposed generalized strategy could be used to prepare different kinds of surface-functionalized PLNPs with control of size, hydrophilicity, and colloidal stability and enhanced/prolonged persistent luminescence for diverse potential applications.